2017
DOI: 10.1186/s12885-017-3460-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the location of cancer stem cell marker CD133 on the prognosis of hepatocellular carcinoma patients

Abstract: BackgroundCD133 (prominin-1) is widely believed to be a cancer stem cell marker in various solid tumor types, and CD133 has been correlated with tumor-initiating capacity. Recently, the nuclear location of CD133 expression in tumors has been discussed, but hepatocellular carcinoma (HCC) has not been included in these discussions. The goal of this study was to investigate the location of CD133 expression in HCC and this location’s potential value as a prognostic indicator of survival in patients with HCC.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…We found significantly higher levels of EPCAM and CD133 mRNA and protein in DPHCC tissues than in non-DPHCC tissues. Our results are consistent with reports that HCC patients positive for EpCAM or CD133 have poor prognosis, and that EPCAM and CD133 act synergistically in tumors [30][31][32] . EPCAM participates in a Wnt signaling pathway of tumorigenesis 33,34 , while CD133+ cancer cells up-regulate interleukin-8 (IL-8) and activate MAP kinase signaling pathways 35,36 .…”
Section: Discussionsupporting
confidence: 93%
“…We found significantly higher levels of EPCAM and CD133 mRNA and protein in DPHCC tissues than in non-DPHCC tissues. Our results are consistent with reports that HCC patients positive for EpCAM or CD133 have poor prognosis, and that EPCAM and CD133 act synergistically in tumors [30][31][32] . EPCAM participates in a Wnt signaling pathway of tumorigenesis 33,34 , while CD133+ cancer cells up-regulate interleukin-8 (IL-8) and activate MAP kinase signaling pathways 35,36 .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Ding et al demonstrated that CD133 pos liver cancer cells were resistant to transforming growth factor β (TGF-β)-induced apoptosis and this effect could be blunted using a mitogen-activated protein kinase 1 (MEK1) inhibitor [ 109 ]. Interestingly, a recent study indicated that the location of CD133 on the CSC may play an important role on the aggressiveness of the cancer and the prognosis of the liver cancer patient [ 110 ]. This study analyzed cancerous tissues and pair-matched adjacent normal liver tissues from 119 hepatocellular carcinoma patients and revealed that cytoplasmic CD133 expression was correlated with poor prognosis, while nuclear CD133 expression was correlated with favorable prognosis.…”
Section: Cd133 As a Csc Markermentioning
confidence: 99%
“…Multiple clinical studies had shown that the high expression of CSC marker CD133 in HCC tissues, in particular in the cytoplasm, is correlated with a poor prognosis [47][48][49][50][51] . In addition to prognosis, CD90 is highexpressed in HCC nodule [52] and is correlated with HCC differentiation grades [53,54] .…”
Section: Relevance Of Csc Markers In Clinicopathological Feature Of Hccmentioning
confidence: 99%